Macroeconometric forecasting using a cluster of dynamic factor models - Christian Glocker; Serguei Kaniovski (Austrian Institute of Economic Research (WIFO), 2020)
We propose a modelling approach involving a series of small-scale factor models. They are connected to each other within a cluster, whose linkages are derived from Granger-causality tests. GDP forecasts are established across the production, income and expenditure accounts within a disaggregated approach. This method merges the benefits of large-scale macroeconomic and small-scale factor models, rendering our Cluster of Dynamic Factor Models (CDFM) useful for model-consistent forecasting on a large scale. While the CDFM has a simple structure, its forecasts outperform those of a wide range of competing models and of professional forecasters. Moreover, the CDFM allows forecasters to introduce their own judgment and hence produce conditional forecasts.
Keywords: C22; C53; C55; E37; 330; Forecasting; Dynamic factor model; Granger causality; Structural modeling